2020
DOI: 10.2174/1574893615999200425225729
|View full text |Cite
|
Sign up to set email alerts
|

GASPIDs Versus Non-GASPIDs - Differentiation Based on Machine Learning Approach

Abstract: Background: Peptidases are a group of enzymes which catalyzes the cleavage of peptide bonds. Around 2-3% of the whole genome codes for proteases and about one third of all known proteases are serine proteases which are divided into 13 clans and 40 families. They are involved in diverse physiological roles such as digestion, coagulation of blood, fibrinolysis, processing of proteins and prohormones, signaling pathways, complement fixation and have a vital role in immune defense system. Based on their functions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…As much as machine learning-based methods like those mentioned above are capable of delivering good results, it has been shown that deep learning models produce better results without requiring a manual feature extraction operation. Furthermore, machine learning techniques for genomics analysis still require input features that are hand-designed by an individual and extracted from predetermined sequences of input data in order to be able to make decisions [17,18]. It should be noted, however, that convolutional neural networks (CNNs) are able to quickly extract substantial features from a variety of stages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As much as machine learning-based methods like those mentioned above are capable of delivering good results, it has been shown that deep learning models produce better results without requiring a manual feature extraction operation. Furthermore, machine learning techniques for genomics analysis still require input features that are hand-designed by an individual and extracted from predetermined sequences of input data in order to be able to make decisions [17,18]. It should be noted, however, that convolutional neural networks (CNNs) are able to quickly extract substantial features from a variety of stages.…”
Section: Introductionmentioning
confidence: 99%
“…In the case that the proposed sequence did not meet all of these criteria, the sequence was referred to as a non-enhancer sequence. The analysis in this study was based on Chou's five-step rule, which has been extensively used in recent studies [17][18][19][20]. As required, the following procedures were followed: (i) for the preparation and testing of the indicator, the large benchmark dataset must be assembled and analyzed; (ii) enhance the significance of genomic sequences by emphasizing a meaningful pattern during the extraction or determination; (iii) develop a classifier capable of identifying these sequences in an effective and accurate manner; (iv) perform various cross-validation techniques on the data; and (v) assemble a web server.…”
Section: Introductionmentioning
confidence: 99%
“…The serine proteases involved in immune defense i.e. apoptosis, cytokine & inflammatory responses and direct killing of pathogens via phagosomes [2,7,14], are more commonly known as GASPIDs (Granules Associated Serine Peptidases of Immune Defense) [2] Whereas, the non-immunological serine proteases involved in digestion, blood coagulation, fibrinolysis, development, and fertilization are recently been referred to as non-GASPIDS [14].…”
Section: Introductionmentioning
confidence: 99%